Development of Electronic Student Worksheets Based Local Potential to Enhance Students’ Science Learning Outcomes - Fatmawati Fatmawati*; Muhammad Rivaldi; Suhaeni Suhaeni (JIPI (Jurnal IPA dan Pembelajaran IPA), 2023)
Facilities need in the learning process; among the conveniences that can are the application of flexible teaching materials such as electronic student worksheets (E-LKPD). Student worksheets that apply in schools are still general. Good student worksheets are attractive and increase student insight. The study aimed to examine learners' feasibility and response to E-LKPD based on local potential. This research used the development model of ADDIE  (analysis, design, development, implementation, evaluation). E-LKPD feasibility was assessed based on the average assessment result by material experts, media experts, and practitioners (teachers) with a feasibility percentage of 87,51, classified as very feasible. Learner's response obtained from average assessment on learners' response in big scale test with a percentage of 78,31, classified as attractive. This statement implies that    E-LKPD-based local potential was feasible for use in learning.